LANGUAGE SHIFT AND HERITAGE LANGUAGE MAINTENANCE AMONG INDONESIAN YOUNG GENERATIONS: A CASE STUDY OF PAMULANG UNIVERSITY STUDENTS (Universitas Pamulang, 2020)
This paper aims to analyze language shift and heritage language maintenance among Indonesian young generation, a case study of Pamulang University students. Based on that purpose, this study conducted some research in analyzing effort to maintain the heritage language, analyzing the strategy used in maintaining heritage language, and identifying factors contribute to language loss among students. The study used a descriptive qualitative research design approach involving an open-ended questionnaire consisted of open-ended questions. The result of this study revealed that even though they live on a small scale of their native community, yet, they can maintain their local language. Thus, it can not be denied that youth people tend to shift the language due to globalization and the embracing of technology. In conclusion, it can be inferred that most students of Unpam use their local language and Bahasa Indonesia at the same level. Many of them still use local language when communicating with their parents and family members around them as well as Bahasa Indonesia. Suek suggested a solution to this problem that the community should be related to the use of language and attitudes in which mostly happen in school and family. It is hoped when children get used to a local language, they will also become aware of how important the native language as showing their identity in their environment and nationality.Keywords: Language Shift, Language Maintenance, Heritage Language, Language Preservation.